The Linguistic Integration of Adult Migrants / L'intégration linguistique des migrants adultes Some lessons from research / Les enseignements de la recherche - Beacco, Jean-Claude; Krumm, Hans-Jürgen (De Gruyter, 2017)
This volume provides a comprehensive report on a symposium organised by the Council of Europe (Strasbourg) in 2016 in the context of its human rights agenda. Its purpose was to explore some of the ways in which scientific evidence can inform the development and implementation of policy and practice designed to support the linguistic integration of adult migrants